Gap junctions modulate survival-promoting effects of fibroblast growth factor-2 on cultured midbrain dopaminergic neurons - Leung, Doreen Siu Yi; Unsicker, Klaus; Reuss, Bernhard (Molecular and cellular neuroscience, 2001)
Fibroblast growth factor 2 (FGF-2) and glial cell line-derived neurotrophic factor (GDNF) support survival of dopaminergic midbrain neurons. Neurons are coupled by gap junctions, propagating metabolites and intracellular second messengers possibly mediating growth factor effects. We asked, therefore, whether gap junctions influence the survival-promoting effects of FGF-2 and GDNF. RT-PCR, Western blotting, and immunocytochemistry demonstrate that FGF-2 but not GDNF upregulates cx43 mRNA and immunoreactivity in rat embryonic day 14 midbrain cultures, whereas cx26, cx32, and cx45 were unchanged. In addition, functional coupling as assayed by the spread of neurobiotin was increased by FGF-2. Furthermore, the gap junction blocker oleamide abolished survival-promoting effects of FGF-2 on dopaminergic midbrain neurons. Together, these results support a direct role of gap junction communication for survival-promoting effects of FGF-2 on dopaminergic midbrain neurons, making gap junction communication a substantial parameter for neuron survival.